PENGARUH TEH KOMBUCHA TERHADAP KEKERASAN ENAMEL: EFFECT OF KOMBUCHA TEA ON ENAMEL HARDNESS - Trimurni Abidin; Mita Zahara Hutagalung (TALENTA, 2010)
Kombucha tea is a beverage product obtained by the fermentation of sugared tea with Kombucha starter. Kombucha tea believed as a healthy beverage. Healthy beverage kombucha tea consumed for its beneficial effects on human health. Kombucha tea is a beverage product contains of acid. Demineralisation can be happened when enamel is in acid environ-ment. Kombucha tea consists of green tea that contain of fluor can increase the surface hardness of enamel. The aim of this study was to know the influence of kombucha tea on the surface hardness of enamel. Kombucha tea consists of 5 grs green tea, aquadest, sugar and kombucha starter with fermentation for 7 days. Thirty mandibular premolars were randomly divided into three groups. The first group was immersed in aquadest as negative control, the second group in the green tea as positive control and the last group in combucha tea, for 30, 60 and 120 minutes. The surface hardness measurement was done before and after immersion using Micro Vickers Hardness Tester. Data was analyzed using ANOVA. The results showed that in all of the aquadest and green tea groups were not significantly different influence the surface hardness measurement between before and after immersion for 30, 60 and 120 minutes (p > 0.05). Kombucha tea groups showed significant influence the surface hardness measurement between before and after immersion for 30, 60 and 120 minutes (p < 0.05). It was concluded that the immersion in combucha tea for 30, 60 and 120 minutes could increase the surface hardness of enamel.